Erythropoietin in children i. findings in hodgkin’s disease - Çıtıpıtıoğlu, Belma (The Turkish Journal of Pediatrics, 1972)
Seventeen children with Hodgkin’s Disease were subjected to erythropoietin assays to establish a relationship between this disease and the erythropoietic activity. Six of the seventeen cases were observed to have an increased erythropoietic activity. We were not able to determine a positive relationship between the production of erythropoietin and the level of anemia. The presence of other possible factors contributing to the increased activity of erythropoietin have been suggested.